Investigating the relationship between social media addiction and mental health - Hammad, Mohammad Ahmed; Awed, Huda Shaaban (Nurture, 2023)
Objective: The main objective of this study was to determine the percentage of young people addicted to social media at Najran University. A significant rise in mental health problems among young people has led to increased interest in the relationship between social media and mental health. Therefore, it was important to identify the relationship between social media use and mental health in young people. Design/Methodology/Approach: Data was collected from 330 students at Najran University. The average age of the sample ranged from M = 21.1 years to SD = 2.52 years. The Bergen Social Media Addiction Scale, the Centre for Epidemiological Studies Depression Scale and the De Jong Gierveld 6-item loneliness scale were used. Results: The results showed that 60.30% of the participants are addicted to social media. Statistically significant differences were also found between social media addicts and non-social media addicts. Linear regression analysis also showed that internet addiction could be predicted by the variables depression, anxiety and loneliness. Conclusion: The results indicate the importance of spreading psychological awareness of the risks associated with social media addiction and the psychological damage it brings. Organising seminars and awareness lectures on the impact of social media addiction on students.